Engineering Betalain Biosynthesis in Tomato for High Level Betanin Production in Fruits - Grützner, Ramona; Schubert, Ramona; Horn, Claudia; Yang, Changqing; Vogt, Thomas; Marillonnet, Sylvestre (Frontiers in Plant Science, 2021)
Betalains are pigments found in plants of the Caryophyllales order, and include the red-purple betacyanins and the yellow-orange betaxanthins. The red pigment from red beets, betanin, is made from tyrosine by a biosynthetic pathway that consists of a cytochrome P450, a L-DOPA dioxygenase, and a glucosyltransferase. The entire pathway was recently reconstituted in plants that do not make betalains naturally including potato and tomato plants. The amount of betanin produced in these plants was however not as high as in red beets. It was recently shown that a plastidic arogenate dehydrogenase gene involved in biosynthesis of tyrosine in plants is duplicated in Beta vulgaris and other betalain-producing plants, and that one of the two encoded enzymes, BvADHα, has relaxed feedback inhibition by tyrosine, contributing to the high amount of betanin found in red beets. We have reconstituted the complete betanin biosynthetic pathway in tomato plants with or without a BvADHα gene, and with all genes expressed under control of a fruit-specific promoter. The plants obtained with a construct containing BvADHα produced betanin at a higher level than plants obtained with a construct lacking this gene. These results show that use of BvADHα can be useful for high level production of betalains in heterologous hosts. Unlike red beets that produce both betacyanins and betaxanthins, the transformed tomatoes produced betacyanins only, conferring a bright purple-fuschia color to the tomato juice.